PENGARUH ADVERTISING VALUE TERHADAP PURCHASE INTENTION YANG DIMEDIASI OLEH BRAND AWARENESS PADA KONSUMEN E-COMMERCE TOKOPEDIA DI KOTA BANDUNG - Cahyani, Selvina; Edi Nurtjahjadi (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
Current developments in information technology are very broad and useful. Technology is not only used for communication, information, or entertainment; it can also be used for other activities, such as online shopping. Indonesian e-commerce has increased from 2021 to 2023, but purchasing intentions have decreased in Tokopedia, Bandung City. The entire research sample consisted of 150 people who participated and were analyzed using the SPSS 26 program. Various tests such as instrument validity and reliability tests, classical assumption tests, simple and multiple regression tests, and the Sobel test were used as analytical tools. The research results show that Advertising Value influences Purchase Intention which is mediated by Brand Awareness with a calculated t value of 2.68149 and a significance value of 0.007.